How to prevent endophthalmitis after intravitreal injections - Goldberg, Roger A (Int J Retina Vitreous, 2015)
Endophthalmitis is an uncommon but often visually devastating complication of intravitreal injections. This commentary reviews the key aspects and technical components of intravitreal injections and how they may relate to the development of endophthalmitis. Because endophthalmitis is a rare event, data are often lacking on specific aspects of injection technique that may or may not be helpful in preventing infection. What is not in doubt, however, is the utmost importance of using povidone-iodine antisepsis to the ocular surface prior to injection, and maintaining a lash and lid margin-free injection site.